Intention of Muslim Millennials to Invest in Islamic Peer-to-Peer Lending in Indonesia - Ajija, Shochrul Rohmatul; Salama, Sri Cahyaning Umi (Universitas Airlangga, 2024)
Fintech Peer-to-peer (P2P) lending sharia is an evolution of sharia financial institutions through the use of technology in its operational processes. The millennial generation who grew up with technology has a greater talent in utilizing technology and has deeper insights compared to the previous generation. The purpose of this study is to analyze the determinants that influence Muslim millennials to invest in the Islamic P2P lending sector and determine strategies to improve its effectiveness. Latent variables Attitude Towards Behavior (AT), Subjective Norm (SN), Perceived Behavioral Control (PBC), Financial Literacy (FL), and Behavioral Intention (BI) are selected and analyzed using Structural Equation Modeling (SEM) using SmartPLS. This study used an accidental sampling method which was carried out for 30 days of data collection, where 200 respondents were collected. The respondents were specifically the millennial Muslim generation who had invested in financial institutions at least once. The results showed that all latent variables had a significant influence and PBC had the largest contribution. There are three latent variables that have a significant positive effect on BI, namely AT, PBC, and FL. Meanwhile, only SN has a significant negative effect on BI. Therefore, it is necessary to increase literacy in the Indonesian community. Regulators and implementers must collaborate and synergize in improving Islamic financial literacy in Indonesia. For further research development, other variables or samples from different groups can be used to further enrich literacy in Islamic P2P lending.